Beyond the Chains of Dogma: Reconceiving the Divine in Contemporary Philosophy and Islamic Thought - Setiawan, Ahmad Bayu; Saeyd Rashed Hasan Chowdury (Faculty of Ushuluddin and Philosophy, 2024)
The main academic issue in this article is how contemporary philosophy can contribute to the study of religion, particularly Islamic philosophy, by freeing religious thought from the constraints of dogmatic theology. This article discusses efforts to free God from the shackles of theology in the continental and analytic philosophical traditions. Beginning with Meister Eckhart’s prayer expressing a desire to be freed from God, this article traces the connection between Derrida’s deconstruction and logocentrism, which views God as an entity bound by the limitations of language. Based on the thoughts of Derrida, Lyotard, and Irigaray, this article argues that the desire for a God that transcends metaphysics is rooted in the limitations of language in describing the Divine. The research method used is a conceptual analysis of contemporary philosophical theories and their application in the context of Islamic philosophy. This research affirms that true thinking is not only about thinking about God but also about experiencing a direct encounter with Him, where human consciousness is surprised by His presence. The latest trends in philosophy show an effort to liberate Islamic philosophy from orthodox theology so that in the future, religious philosophy can develop by celebrating heterodox understandings and opening space for more diverse religious experiences.